2021
DOI: 10.2147/ndt.s309818
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 5-HT6 Receptor Ligands Combined with Haloperidol or Risperidone on Antidepressant-/Anxiolytic-Like Behavior and BDNF Regulation in Hippocampus and Prefrontal Cortex of Rats

Abstract: Background The presence of depressive and anxiety symptoms in patients with schizophrenia may have an important impact on treatment and compliance. Hence, interventions addressing such comorbidity in schizophrenia should be explored. One target may be a serotonergic 5-HT 6 receptor (5-HT 6 R) since its ligands displayed antidepressant- and anxiolytic-like activities in preclinical experiments. Methods Acute and chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 85 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…Haloperidol (TargetMol, Boston, MA, USA), risperidone (TargetMol), olanzapine (TargetMol), WAY-181187 (oxalate; Tocris Bioscience, Bristol, UK), and SB-742457 (TargetMol) were used in the experiment. Doses of APDs (haloperidol 0.5 mg/kg, risperidone 0.5 mg/kg, and olanzapine 5 mg/kg) and 5-HT 6 ligands (WAY-181187 3 mg/kg and SB-742457 3 mg/kg) were selected for the experiments, based on literature review and our previous studies which presented their separate and combined behavioral effects [ 54 ]. The compounds were suspended in a 1% solution of Tween 80 (Sigma Aldrich, St. Louis, MO, USA) immediately before administration and injected intraperitoneally (ip) in a volume of 2 mL/kg.…”
Section: Methodsmentioning
confidence: 99%
“…Haloperidol (TargetMol, Boston, MA, USA), risperidone (TargetMol), olanzapine (TargetMol), WAY-181187 (oxalate; Tocris Bioscience, Bristol, UK), and SB-742457 (TargetMol) were used in the experiment. Doses of APDs (haloperidol 0.5 mg/kg, risperidone 0.5 mg/kg, and olanzapine 5 mg/kg) and 5-HT 6 ligands (WAY-181187 3 mg/kg and SB-742457 3 mg/kg) were selected for the experiments, based on literature review and our previous studies which presented their separate and combined behavioral effects [ 54 ]. The compounds were suspended in a 1% solution of Tween 80 (Sigma Aldrich, St. Louis, MO, USA) immediately before administration and injected intraperitoneally (ip) in a volume of 2 mL/kg.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have demonstrated the antidepressant and anxiolytic effects of two specific 5-HT6 receptor agonists in rodents (Carr et al, 2011 ). The 5-HT6 receptor agonists enhanced the effects of haloperidol and reduced the haloperidol-induced side effects (Wesołowska et al, 2021 ). Furthermore, 5-HT6 receptor antagonists such as SB-399885 have been shown to have antidepressant effects in animal studies.…”
Section: Serotonin and Its Receptorsmentioning
confidence: 99%
“…Paradoxical results are explained by the specific modulation of cerebral neurocircuits by different 5-HT6 receptor agonists or antagonists. Further studies are needed to clarify the brain region specificity of 5-HT6 receptors and their implication in depression (Wesołowska et al, 2021 ).…”
Section: Serotonin and Its Receptorsmentioning
confidence: 99%